Syaria Factoring: A Shariah-Compliant Trade Finance Solution for SMEs - Al-farishi, Salman (Islamicate Institute, 2019)
This study investigates Syaria factoring as a shariah-compliant alternative to conventional factoring for small and medium enterprises (SMEs). Drawing from Islamic commercial jurisprudence and institutional finance, it constructs a conceptual model using wakalah, murabahah, and ijarah contracts to provide liquidity while maintaining shariah integrity. Unlike conventional factoring, which involves interest and risk transfer, Syaria factoring offers ethical, transparent, and risk-sharing mechanisms. Through qualitative documentary analysis, the research compares Syaria and conventional models, identifies operational structures, and evaluates its impact on SME financing and the Islamic finance sector. Findings confirm that Syaria factoring supports financial inclusion, aligns with maqasid al-shariah, and strengthens the Islamic finance ecosystem. The study concludes with policy and institutional recommendations to standardize, regulate, and promote Syaria factoring as a key ethical finance innovation. It contributes to bridging theoretical, practical, and regulatory gaps in Islamic financial product development.